A novel muscle LIM-only protein is generated from the paxillin gene locus in Drosophila. - Yagi, R.; Ishimaru, S.; Yano, H.; Gaul, U.; Hanafusa, H.; Sabe, H. (EMBO Reports, 2001)
Paxillin is a protein containing four LIM domains, and functions in integrin signaling. We report here that two transcripts are generated from the paxillin gene locus in Drosophila; one encodes a protein homolog of the vertebrate Paxillin (DPxn37), and the other a protein with only three LIM domains, partly encoded by its own specific exon (PDLP). At the myotendinous junctions of Drosophila embryos where integrins play important roles, both DPxn37 and PDLP are highly expressed with different patterns; DPxn37 is predominantly concentrated at the center of the junctions, whereas PDLP is highly enriched at neighboring sides of the junction centers, primarily expressed in the mesodermal myotubes. Northern blot analysis revealed that DPxn37 is ubiquitously expressed throughout the life cycle, whereas PDLP expression exhibits a biphasic pattern during development, largely concomitant with muscle generation and remodeling. Our results collectively reveal that a unique system exists in Drosophila for the generation of a novel type of LIM-only protein, highly expressed in the embryonic musculature, largely utilizing the Paxillin LIM domains.